(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines modern technologies for the production of fractured road products from natural stone, their operational characteristics, and usage prospects. An analysis is provided on the advantages of various types of stone, such as granite, basalt, limestone, and sandstone, as well as the risks and limitations associated with their use. Special attention is paid to the automation of processes, the introduction of innovative technologies, and the development of generalized production management models. Graphic data is presented illustrating the relationship between efficiency and cost as a function of production volume. The article emphasizes the importance of environmental aspects and sustainability in the stone mining industry.